2016
DOI: 10.1016/j.rmed.2016.08.025
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of asthma and polycystic ovary syndrome: A concise review

Abstract: Asthma may be associated with polycystic ovary syndrome (PCOS), and possibly patients with PCOS have a more severe type of asthma. The purpose of this systematic literature review is to summarize evidence of a coexistense of PCOS and asthma using the available literature. The search was completed on 01.01.2016. English language articles were retrieved using the search terms 'Asthma' AND 'PCOS', 'Asthma' AND 'systemic inflammation', 'Asthma' AND 'metabolic syndrome', 'asthma' AND 'gynaecology', 'PCOS' AND 'syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 48 publications
(43 reference statements)
1
14
1
1
Order By: Relevance
“…Our results confirm the literature that has reported that PCOS is independently associated with asthma [20,23,39]. The relationship between asthma and PCOS is likely to be multifactorial, but there are mechanisms proposed that could explain the association.…”
Section: Discussionsupporting
confidence: 91%
“…Our results confirm the literature that has reported that PCOS is independently associated with asthma [20,23,39]. The relationship between asthma and PCOS is likely to be multifactorial, but there are mechanisms proposed that could explain the association.…”
Section: Discussionsupporting
confidence: 91%
“…obese women or women with a metabolic syndrome have an increased TTP [30, 31]. Metabolic syndrome is a part of polycystic ovary syndrome (PCOS), and Zieraua et al , in meta-analyses, confirmed that asthma may be associated with PCOS, and women with PCOS have a more severe type of asthma [32]. Also, an interesting observation is the fact that a greater number of females undergoing in vitro fertility (IVF) treatment were using anti-asthmatic drugs [33].…”
Section: Time To Pregnancy (Ttp)mentioning
confidence: 99%
“…Currently, the incidence of asthma among PCOS patients still remains controversial. In recent years, more than a dozen articles from different countries have reported the prevalence of asthma in PCOS patients [26][27][28] . However, due to the differences in race, population, patient age, BMI and other factors, the results were not consistent.…”
Section: Discussionmentioning
confidence: 99%